EVALUATION OF THE CORPORATE SOCIAL RESPONSIBILITY REPORTING OF THE CO-OPERATIVE GROUP FOOD RETAIL DIVISION - Rizo Patron Pinto, Cecilia Ursula (2005)
Corporate Social Responsibility (CSR) reporting is now a critical element in communicating a company's social and environmental policies to the investment community and other stakeholder populations.